Integrating Pre-Exposure Prophylaxis Delivery in Public Health Family Planning Clinics: Lessons Learned From a Programmatic Implementation Project in Kenya - Mugwanya, Kenneth K.; Kinuthia, John (Frontiers in Reproductive Health, 2021)
Sexually active African women are a priority population for HIV prevention due to the disproportionately high frequency of new HIV infections. Family planning (FP) clinics offer an already trusted platform that can be used to reach women for HIV prevention services, including pre-exposure prophylaxis (PrEP). In the recent PrEP Implementation in Young Women and Adolescent (PrIYA program), we piloted PrEP implementation in FP clinics in Kisumu, Kenya, and demonstrated that it was possible to integrate PrEP provision in FP systems with a program-dedicated staff. In this perspective, we describe experiences and strategies employed to introduce PrEP implementation in FP clinics and lessons learned. We identified the following lessons for PrEP introduction in FP clinics in Kenya: (1) possible to integrate and generate high enthusiasm for PrEP delivery in FP clinics but persistence on PrEP is a challenge, (2) involvement of national and regional stakeholders is critical for buy-in, contextualization, and sustainability, (3) delivery models that do not integrate fully with existing staff and systems are less sustainable, (4) creatinine testing at PrEP initiation may not be necessary, (5) fully integrated HIV and FP data systems need to be developed, and (6) incorporating implementation science evaluation is important to understand and document effective implementation strategies. In summary, integration of HIV prevention and FP services provides an opportunity to promote one-stop women-centered care efficiently. However, a broader focus on delivery models that utilize existing staff and novel strategies to help women identify their own risk for HIV are needed to ensure greater success and sustainability.